Narramos el proceso histórico del poblamiento de América - Mendez Rodriguez, Janett Silvia (2020)
The lesson entitled " We narrate the historical process of the population of America", designed for third grade of Primary Education, aims to develop in the child his personal identification, recognizing and valuing its history in the area Social Personal considering the approach of Personal and active Citizenship development. The present research work is based on the approach of personal development and active citizenship, with a learning session design relevant to the area, thus ensuring the achievement of the competence Build Your Identity. Likewise, this work is based on two aspects: first the Theoretical Support, which shows the main theoretical bases and finally the Pedagogical Support that supports all the processes applied and developed in the learning session design.